Two-staged treatment of arterio-portal fistula - E. A. Vlasenko; I. V. Khasyanova; S. N. Furkalo; A. V. Grinenko; A. I. Zhilenko (Клінічна хірургія, 2020)
Two-staged treatment of arterio-portal fistula